Regulatory Gaps in Addressing School Bullying in Indonesia: The Need for a Comprehensive Anti-Bullying Framework for Child Protection - Dwi Nur Fauziah Ahmad (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
School bullying is a serious child-protection problem because it combines repeated aggression, a power imbalance, and potentially enduring physical, psychological, educational, and social harm. This article examines whether Indonesia’s current legal architecture provides sufficiently clear and integrated standards for preventing and addressing bullying in schools, and it formulates the essential elements of a comprehensive anti-bullying framework. The study employs doctrinal legal research using statutory, conceptual, and limited comparative approaches. Primary legal materials include child-protection, education, juvenile-justice, criminal, electronic-information, and school-safety regulations, with particular attention to Regulation of the Minister of Primary and Secondary Education No. 6 of 2026. The analysis finds that Indonesia is not experiencing a complete absence of law: general child-protection norms, criminal offences, digital-law provisions, and a renewed safe-school administrative framework are already available. Nevertheless, a material regulatory gap remains because bullying is not uniformly defined in the current framework, its distinguishing elements are not consistently operationalised, and prevention, reporting, evidence preservation, victim recovery, offender rehabilitation, institutional accountability, and cross-sector referral are not governed through one enforceable national standard. The article therefore proposes a child-rights-based and whole-education framework that combines prevention, proportionate accountability, psychosocial recovery, and carefully safeguarded restorative justice. Its principal contribution is to reconceptualise the Indonesian problem as normative fragmentation and operational incompleteness rather than a total legal vacuum, particularly after the 2026 regulatory transition